Interaction, stereotypes and performance: Evidence from South Africa - Lucia Corno; Eliana La Ferrara; Justine Burns (Institute for Fiscal Studies (IFS), 2019)
We exploit a policy designed to randomly allocate roommates in a large South African university to investigate whether inter-racial interaction affects stereotypes, attitudes and performance. Using Implicit Association Tests, we find that living with a roommate of a different race reduces white students' negative stereotypes towards blacks and increases inter-racial friendships. Interaction also affects academic outcomes: blacks in mixed rooms improve their GPA, pass more exams and have lower dropout rates. This positive effect is not driven by the ability of the roommate and is stronger the lower the roommate's prejudice, suggesting a complementarity between stereotype reduction and performance gains.
Keywords: 330